Affective politics after 9/11 - Hall, T; Ross, A (Cambridge University Press, 2015)
Affect and emotion are key elements of our lived experience as human beings but currently play little role in how we theorize actorhood in international relations. We offer six amendments for integrating affective dynamics into existing conceptions of individual-level actorhood in IR. From these amendments emerge the theoretical micro-foundations upon which we build propositions concerning potential collective-level affective dynamics and political strategies. We illustrate the analytical payoff of our proposals by examining the aftermath of the terrorist attacks on 11 September 2001. By amending existing understandings of actorhood to include human affective experience, we can integrate and make sense of a variety of psychological, social, and political consequences stemming from the attacks, both within the United States and internationally.